pls give me the right answer of this question
![](https://hi-static.z-dn.net/files/d03/c3b0ba173d9873fef9622ed9058f2222.jpg)
Answers
Step-by-step explanation:
1) 0 and 2) 7.5
Answer:
1
Combine multiplied terms into a single fraction
3
4
(
3
+
2
)
−
2
=
2
+
2
\frac{3}{4}(3x+2)-2=2x+2
43(3x+2)−2=2x+2
3
(
3
+
2
)
4
−
2
=
2
+
2
\frac{3(3x+2)}{4}-2=2x+2
43(3x+2)−2=2x+2
2
Distribute
3
(
3
+
2
)
4
−
2
=
2
+
2
\frac{{\color{#c92786}{3(3x+2)}}}{4}-2=2x+2
43(3x+2)−2=2x+2
9
+
6
4
−
2
=
2
+
2
\frac{{\color{#c92786}{9x+6}}}{4}-2=2x+2
49x+6−2=2x+2
3
Add
2
2
2
to both sides of the equation
9
+
6
4
−
2
=
2
+
2
\frac{9x+6}{4}-2=2x+2
49x+6−2=2x+2
9
+
6
4
−
2
+
2
=
2
+
2
+
2
\frac{9x+6}{4}-2+{\color{#c92786}{2}}=2x+2+{\color{#c92786}{2}}
49x+6−2+2=2x+2+2
4
Simplify
Add the numbers
Add the numbers
9
+
6
4
=
2
+
4
\frac{9x+6}{4}=2x+4
49x+6=2x+4
5
Subtract
2
2x
2x
from both sides of the equation
9
+
6
4
=
2
+
4
\frac{9x+6}{4}=2x+4
49x+6=2x+4
9
+
6
4
−
2
=
2
+
4
−
2
\frac{9x+6}{4}{\color{#c92786}{-2x}}=2x+4{\color{#c92786}{-2x}}
49x+6−2x=2x+4−2x
6
Simplify
Combine like terms
9
+
6
4
−
2
=
4
\frac{9x+6}{4}-2x=4
49x+6−2x=4
7
Multiply all terms by the same value to eliminate fraction denominators
9
+
6
4
−
2
=
4
\frac{9x+6}{4}-2x=4
49x+6−2x=4
4
(
9
+
6
4
−
2
)
=
4
⋅
4
4(\frac{9x+6}{4}-2x)=4 \cdot 4
4(49x+6−2x)=4⋅4
8
Simplify
Distribute
Cancel multiplied terms that are in the denominator
Combine like terms
Multiply by 1
Multiply the numbers
+
6
=
1
6
x+6=16
x+6=16
9
Subtract
6
6
6
from both sides of the equation
+
6
=
1
6
x+6=16
x+6=16
+
6
−
6
=
1
6
−
6
x+6{\color{#c92786}{-6}}=16{\color{#c92786}{-6}}
x+6−6=16−6
10
Simplify
Subtract the numbers
Subtract the numbers
=
1
0
Step-by-step explanation: